Types of Meaning and Meaning Relations: A Semantic Review Based on Leech’s Framework (with Javanese Examples) (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines Leech’s (1981) seven types of meaning and major meaning relations in lexical semantics, using examples from English and Javanese (bahasa Jawa) to demonstrate cross-linguistic relevance. Incorporating traditional Javanese vocabulary (e.g., bocah, wedang, mrene, putihan), the paper illustrates how conceptual, social, affective, and collocative meanings differ across languages. A review of recent studies (2020–2025) is included to compare how scholars analyze semantic categories in contemporary linguistic research.